The Solution for Overcoming Conflicts in the Protection of Applied art works and Industrial designs - Thi Thanh, Dang (VNU Journal of Science: Policy and Management Studies, 2022)
The issue of conflict of intellectual property rights in Vietnam is increasingly common and complicated, especially the conflict between copyright to applied art works and industrial property rights to industrial designs. There have been many studies ahead of research on this issue, but there is a lack of foreign law surveys. This article approaches the problem through a foreign law survey to propose a solution to the conflict between applied art works and industrial designs for Vietnam. Research tasks include: identifying the nature and causes of conflicts, conflict resolution mechanisms in Vietnam's current intellectual property law; points out shortcomings in current Vietnam's intellectual property law; compare with foreign laws and practices to draw lessons applicable to Vietnam. Keywords Applied art works, Industrial designs, Conflicts, Duel protection, independent protection, beneficial balance. References [1] H. L. Phuong, Conflict of Rights in the Protection of Industrial Property Rights among Trademarks, Industrial Designs and Copyrights of Applied Art Works - Lessons Learned from Enterprises in Nghe An, 2017 (in Vietnamese). [2] L. T. N. Giang, Conflict between the Protection of Trademark and Trade Name, Journal of Legal Sciences, Vol. 76, No. 4, 2013, pp. 58-59 (in Vietnamese). [3] N. P. D. Linh, Interference between the Mechanism of Protection of Applied Art Works and Protection of Industrial Designs and Trademarks, Master thesis at Hanoi Law University, 2013 (in Vietnamese). [4] V. T. T. Ha, Regulations of Vietnamese Law on the Phenomenon of Overlapping Intellectual Property Rights between Trademarks, Industrial Designs and Applied Art Works, Community Law Consulting and Teaching Team, 2020 (in Vietnamese). [5] Mondaq, Protecting of Works of Applied Art under Chinese Judicial Practice (Part I), https://www.mondaq.com/china/copyright/207100/protecting-of-works-of-applied-art-under-chinese-judicial-practice-part-/i,/ 2012 (accessed on: October 10th, 2020). [6] China Intellectual Property, Protection of Works of Applied Art in China, http://www.chinaipmagazine.com/en/journal-show.asp?id=805/, 2012 (accessed on: October 10th, 2020). [7] Mondaq, China: Reflections on the Overlapping Protection of Intellectual Property Rights of Applied Works of Art , https://www.mondaq.com/china/intellectual-property/684176/, 2018 (accessed on: October 10th, 2020). [8] The IP Cat, When Does Copyright Protection Arise in Works of Applied Art and Industrial Models and Designs? A New CJEU Reference, https://ipkitten.blogspot.com/2018/01/when-does-copyright-protection-arise-in.html/, 2018 (accessed on: October 11th, 2020). [9] Jiadian Xinwen, The Research of Conflict ad Solutions between the Industrial Right and Copyright, http://www.jiadianxinwen.com/news/20180207/28753.html/, 2018 (accessed on: October 11th, 2020). [10] Lunwen Boom, The Research of Conflict and solutions between the industrial Right and Copyright, http://lunwenboom.com/detail16373/, 2019 (accessed on: October 11th, 2020).